Legal Protection Against Gharar in Sharia E-Commerce: A Consumer Law Analysis in Support of the SDGs - Fatihah Zakiya Aqmal; Muthoifin; Sana Ashraf (Profetika: Jurnal Studi Islam, 2025)
Objective: By comparing the principles of Islamic law contained in the fatwa of DSN-MUI Number 146/DSN-MUI/XII/2021 and Law Number 8 of 1999 concerning Consumer Protection (UUPK), this study aims to analyze the legal protection provided to consumers against gharar (uncertainty) in sharia e-commerce transactions. Theoretical framework: used refers to fiqh muamalah, legal principles contained in the UUPK and in the DSN-MUI Fatwa, as well as the Sustainable Development Goals (SDGs), especially the 12th and 16th SDGs. Literature review: Few studies explicitly address the existence and forms of gharar in sharia e-commerce and its legal consequences, most of which still focus on consumer protection from a normative point of view only. Method: using normative legal analysis, with legislative, conceptual, and comparative approaches, and supported by literature studies. Results: show that although the Consumer Protection Law does not specifically mention the use of the term "gharar", the prohibition against ambiguity, fraud, and failure to fulfill consumer rights has been accommodated with the principles of justice, transparency, and responsibility. In addition to the UUPK, the DSN-MUI fatwa emphasizes the importance of clarity of contracts, clarity of product information, and prohibition of harmful Sharia practices. Implications: This study highlights the need to align Sharia principles with positive law. Emphasizing the need for harmonization between sharia norms and positive law to ensure that consumer protection in Indonesia is formal and substantive, in line with Islamic justice values. Novelty: from this research reveals explicit regulatory loopholes in the UUPK and the disclosure of the form of gharar in the context of sharia e-commerce, which can serve as a basis for national legal policy recommendations based on Islamic principles as well as an integrative approach between sharia values, national law and global development in the context of digital consumer protection.